Large-scale DNA-based phenotypic recording and deep learning enable highly accurate sequence-function mapping - Simon Höllerer (Nature Portfolio, 2020)
Current methods to generate sequence-function data at large scale are either technically complex or limited to specific applications. Here the authors introduce DNA-based phenotypic recording to overcome these limitations and enable deep learning for accurate prediction of function from sequence.